Optimal Photonic Crystal Cavities for Coupling Nanoemitters to Photonic Integrated Circuits. Issue 2 (1st October 2019) - Olthaus, Jan; Schrinner, Philip P. J.; Reiter, Doris E.; Schuck, Carsten
Abstract: Photonic integrated circuits that are manufactured with mature semiconductor technology hold great promise for realizing scalable quantum technology. Efficient interfaces between quantum emitters and nanophotonic devices are crucial building blocks for such implementations on silicon chips. These interfaces can be realized as nanobeam optical cavities with high quality factors and wavelength‐scale mode volumes, thus providing enhanced coupling between nano‐scale quantum emitters and nanophotonic circuits. Realizing such resonant structures is particularly challenging for the visible wavelength range, where many of the currently considered quantum emitters operate, and if compatibility with modern semiconductor nanofabrication processes is desired. Here, it is shown that photonic crystal nanobeam cavities for the visible spectrum can be designed and fabricated directly on‐substrate with high quality factors and small mode volumes. Designs are compared based on deterministic and mode‐matching methods and the latter is found advantageous for on‐substrate realizations. The results pave the way for integrating quantum emitters with nanophotonic circuits for applications in quantum technology. Abstract : Photonic integrated circuits hold great potential for quantum technologies. In the article, three on‐substrate designs for coupling nanoscale quantum emitters to nanobeam photonic crystal cavities are compared. The waveguide‐structures are compatible with modern semiconductor thin‐film technology and have been numerically optimized, fabricated, and experimentally characterized. Best performance in terms of quality factor and mode volume is found for mode‐matching designs.